Anomalies in Asia Pacific Stock Markets: A Re-Examination of the Turn-of-the-Year Effect - Tran, Quang Thien; Huynh, Thanh Nhan (Asian Journal of Economic Modelling, 2022)
This paper examines the turn-of-the-year (TOY) effect in fifteen Asia Pacific stock indices by using an updated dataset. The analysis utilizes the daily datasets spanning from 2000 to 2018. Applying the Ordinary Least Square (OLS) and the Exponential Generalized Autoregressive Conditional Heteroskedastic (EGARCH) approach, the results of this paper suggest that the TOY effect becomes detectable again after the Global Financial Crisis (GFC) in developed markets with the tax year not ending in December. Furthermore, the magnitude of this anomaly diminishes in emerging markets after the GFC, which is consistent with the Efficient Market Hypothesis (EMH). The evidence of the leverage effect in the market volatility shows in negative shocks that it is considerably higher than that of positive shocks for all markets. This phenomenon is more evident in mature markets compared to emerging markets. The positive connection between the leverage effect and stock market volatility is seen with diminishing magnitude during the stable market condition after the GFC.